2008
DOI: 10.1093/ndt/gfn137
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation in clinical haemodialysis: LMWH as a major contributor to bio-incompatibility?

Abstract: Platelet activation, as measured by the up-regulation of CD62p, is an early process, occurring not only within the dialyser, but across the entire length of the ECC. As CD62p remained unaltered after the administration of LMWH 10 min before the actual start of HD, this kind of activation is independent of LMWH. Considering PF4 however, a sharp increment was observed after the administration of LMWH and before the start of HD. This finding suggests that the PF4 release observed early in clinical HD is largely i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 17 publications
3
34
0
2
Order By: Relevance
“…This hypothesis fits with the study of Gritters et al, who previously demonstrated an effect of heparin during HD on proteoglycan-bound PF4 possibly due to LMWH-induced endothelial detachment [16]. VanTeeffelen et al showed in mice that a heparin challenge is associated with increased vascular leakage of dextrans and impaired arteriolar vasodilation during reactive hyperemia, suggesting that competitive binding of heparin to glycocalyx-associated proteins may affect glycocalyx barrier properties [29].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This hypothesis fits with the study of Gritters et al, who previously demonstrated an effect of heparin during HD on proteoglycan-bound PF4 possibly due to LMWH-induced endothelial detachment [16]. VanTeeffelen et al showed in mice that a heparin challenge is associated with increased vascular leakage of dextrans and impaired arteriolar vasodilation during reactive hyperemia, suggesting that competitive binding of heparin to glycocalyx-associated proteins may affect glycocalyx barrier properties [29].…”
Section: Discussionsupporting
confidence: 86%
“…Given the effects of hemodialysis (HD) on platelet activation, and due to the highly dynamic blood-ESL interaction, it can be hypothesized that HD may also have acute effects on the ESL [14,15,16]. However, it is unknown whether ESL damage is exacerbated even during the HD treatment in patients with end-stage renal disease (ESRD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leitienne et al [19] showed that the proinflammatory mediator release during hemodialysis depends on heparin dose. In addition, Gritters et al [20] found that myeloperoxidase and platelet factor 4 were released into the systemic circulation directly after the infusion of heparin before connection of the extracorporeal circuit. These and other studies suggest that inflammatory mediators may not only arise from neutrophils and platelets, but also from endothelial cells [21] .…”
Section: Patient and Kidney Survivalmentioning
confidence: 99%
“…With respect to platelets (PLTs), during HD both an increase in the expression of cell surface molecules and the release of intragranular substances has been well documented. Recently, we showed that the upregulation of the PLT surface marker P-selectin (CD62p) is an early process, occurring over the entire length of the extracorporeal circuit (ECC) [2] . Of the many PLT granule products that may increase during the course of HD, Gritters-van platelet factor 4 (PF4) and ␤ -thromboglobulin (BTG) are well documented [3] .…”
Section: Introductionmentioning
confidence: 99%